The Effect Of Adding Monensin Sodium In Feed And Amoxycilin On Digestive Tract Features Of Super Native Chickens - Kabes, Joice Roselfine; Datta, Frans Umbu; Ndaong, Nemay A. (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2025)
Super native chickens are the result of a cross between native chickens (free-range) and laying breeds. The rapid growth of super native chickens cannot be separated from the feeding during its maintenance. The high cost of feed is one of the main challenges in raising chickens. Therefore, in order to increase feed efficiency, one alternative that is often used is the use of Antibiotic Growth Promoters (AGP). AGPs that can be used as additives in chicken rations are monensin and amoxicillin. This type of research is quantitative research with experimental methods, using a completely randomized design (CRD) consisting of 5 treatments (P0, P1, P2, P3, P4) and 20 replicates, so there are 100 super native chickens used in this study. But only 5 chickens from each treatment will be taken. Data analysis used is Analysis of Variance with the results of the analysis presented in tabular form. Based on the results obtained statistically, the provision of monensin sodium and amoxicillin as feed additives did not have a significant effect on the weight of the gizzard and proventriculus and the length of the proventriculus, duodenum, jejenum and ileum. However, monensin sodium and amoxicillin as feed additives had a significant effect on intestinal weight. The results obtained are influenced by various factors.